2014
DOI: 10.2215/cjn.11291113
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Two Catheter Locking Solutions to Reduce Catheter-Related Bloodstream Infection in Hemodialysis Patients

Abstract: Background and objectives Infection is the second leading cause of death in hemodialysis patients. Catheterrelated bloodstream infection and infection-related mortality have not improved in this population over the past two decades. This study evaluated the impact of a prophylactic antibiotic lock solution on the incidence of catheter-related bloodstream infection and mortality.Design, setting, participants, & measurements This prospective, multicenter, observational cohort study compared the effectiveness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
3
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 23 publications
2
61
3
4
Order By: Relevance
“…43 A prospective, observational cohort study in 555 patients conducted over a 3-year period showed a 73% reduction in CRBSI after a gentamicin citrate locking solution was instituted. 47 A unique feature of this study was the decrease in mortality after AML was initiated with an adjusted hazard ratio of 0.32 (CI 0.14-0.75). The rate of gentamicin-resistant organisms actually decreased over the course of the study.…”
Section: Prophylactic Intraluminal Antimicrobial Lock Therapymentioning
confidence: 84%
“…43 A prospective, observational cohort study in 555 patients conducted over a 3-year period showed a 73% reduction in CRBSI after a gentamicin citrate locking solution was instituted. 47 A unique feature of this study was the decrease in mortality after AML was initiated with an adjusted hazard ratio of 0.32 (CI 0.14-0.75). The rate of gentamicin-resistant organisms actually decreased over the course of the study.…”
Section: Prophylactic Intraluminal Antimicrobial Lock Therapymentioning
confidence: 84%
“…Despite the potential benefits of saline solution, the change in clinical practice for a normal saline solution has not been widely suggested in the literature for the whole typology of patients and CVC. A possible explanation for this may be attributed to the long period of time that CVC remains in the patient (25)(26)(27) , complications associated with maintaining CVC (28)(29)(30)(31) , type of infusion used (medicinal, solutions…) (32) ; if the purpose of the CVC is hemodialysis (9)(10)(11)(12)(13)(14) and institutional procedures for locking and flushing can strengthen medical belief about heparin effectiveness (10) , thus ultimately leading to exploiting the effectiveness of other solutions (33) (i.e. citrate).…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of CJASN, Moore et al try to answer these questions (20). The authors conducted a prospective, multicenter, observational cohort study in a metropolitan area to compare the effectiveness of a gentamicin-citrate lock versus heparin in 555 hemodialysis patients undergoing dialysis with a tunneled central venous catheter between 2008 and 2011.…”
mentioning
confidence: 99%